2014
DOI: 10.1055/s-0033-1360198
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 2,3,4′,5-Tetrahydroxystilbene-2-O-β-D-Glucoside on Pressure Overload-Induced Cardiac Remodeling in Rats and Its Possible Mechanism

Abstract: The aim of the present study was to investigate the effects of 2,3,4',5-tetrahydroxystilbene-2-O-beta-D-glucoside, an active component extracted from Polygonum multiflorum, on pressure overload-induced cardiac remodeling in rats. A rat model with cardiac remodeling was induced by abdominal aortic banding. 2,3,4',5-Tetrahydroxystilbene-2-O-beta-D-glucoside (30, 60, 120 mg/kg/day) was administered 3 days after abdominal aortic banding and continued for 30 days. The abdominal aortic banding-treated rats had signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…These data suggest that TSG had a promising anti-aging effect by regulation of Klotho expression [19]. TSG is a free radical-scavenger [22], and exerts anti-aging effects in mammals via a neural insulin/IGF-1 signaling pathway [19]. TSG exhibits strong anti-oxidative and anti-inflammatory effects, as well as protecting mammals from cerebral ischemia and/or reperfusion injury [23, 43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that TSG had a promising anti-aging effect by regulation of Klotho expression [19]. TSG is a free radical-scavenger [22], and exerts anti-aging effects in mammals via a neural insulin/IGF-1 signaling pathway [19]. TSG exhibits strong anti-oxidative and anti-inflammatory effects, as well as protecting mammals from cerebral ischemia and/or reperfusion injury [23, 43].…”
Section: Discussionmentioning
confidence: 99%
“…2, 3,5, 4’-tetrahydroxystilbene-2-O- β -D-glycoside (TSG) is the main bioactive ingredient extracted from the traditional Chinese medicinal herb Polygonum multiflorum Thunb which has been used safely in China for approximately two millennia, and has been reported to have a wide spectrum of pharmacologic functions. TSG has been reported to help people live longer [18], protect impaired neural networks [19], improve blood flow [20], attenuate inflammatory responses [21], prevent the production of oxygen radicals and protect against oxidized LDL-induced endothelial dysfunction [22]. Previously, we demonstrated that TSG inhibits lysophosphatidylcholine (LPC)-induced apoptosis of human umbilical vein endothelial cells (HUVECs) by activating glutathione peroxidase and superoxide dismutase, clearing intracellular reactive oxygen species (ROS), and reducing lipid peroxidation [21, 23].…”
Section: Introductionmentioning
confidence: 99%
“…C57Bl/6 mice were orally gavaged with TSG at a dose of 60 mg/kg body weight per day for 2 weeks. The TSG dose was selected based on previous studies [16,27,28] . Two weeks after the treatment, MI/R surgery was performed as previously described [29] .…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Recent progresses suggested that TSG might have much pharmacological properties including antioxidant, anti-aging, antiinflammation, anti-atherosclerosis, anti-hyperlipidaemia, anti-platelet activity, ameliorate diabetic nephropathy, neuroprotection, hair growth, and cardioprotective effects [47][48][49][50][51][52][53][54][55][56][57][58] . There are increasing reports about the roles of TSG on learning and memory changes of animal AD models, as well as possible action mechanisms.…”
Section: Multiple Target Effects Of Tsg On Alzheimer's Disease Treatmentmentioning
confidence: 99%